2019
DOI: 10.26717/bjstr.2019.14.002543
|View full text |Cite
|
Sign up to set email alerts
|

Airways Surface Liquid and Ion Transport - The Mechanism Maintained Patency

Abstract: The airway epithelium is covered with a thin, liquid protective layer -Airways Surface Liquid (ASL), which is a hydrogel, 3-50μm thick. ASL is created and maintained by water (AQPs) and ion transport, especially sodium (ENaC), chloride (CFTR, ClC), potassium, bicarbonate and calcium. Epithelial cells secrete mucins, which role is to transport ASL towards the upper airways. ASL is the first protection mechanism against solid particles and microorganisms inhaled with air. The proper ASL hydration and functioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 29 publications
0
6
0
3
Order By: Relevance
“…The height of the ALF or ASL and hydration of the periciliary liquid layer depend on opposing mechanisms in water transport: the outward chloride (Cl − ) secretory transport through apical chloride channels (CFTR and CACC mediated), and the inward movement of water following active (re)absorption of Na + through apical sodium channels ENaC. These ion transporting actions occur in concertation with the basolateral Na + /K + -ATPase, located in the ciliated cells [62][63][64]. Whereas several more ion transport processes are involved, Na + and Cl − are the main drivers of the fluid movements.…”
Section: Mechanistic (Physicochemical) Effects and In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The height of the ALF or ASL and hydration of the periciliary liquid layer depend on opposing mechanisms in water transport: the outward chloride (Cl − ) secretory transport through apical chloride channels (CFTR and CACC mediated), and the inward movement of water following active (re)absorption of Na + through apical sodium channels ENaC. These ion transporting actions occur in concertation with the basolateral Na + /K + -ATPase, located in the ciliated cells [62][63][64]. Whereas several more ion transport processes are involved, Na + and Cl − are the main drivers of the fluid movements.…”
Section: Mechanistic (Physicochemical) Effects and In Vitro Studiesmentioning
confidence: 99%
“…(5) Interaction with ENaC. As already discussed, ENaC is the main mechanism for maintaining the height of ASL and regulating the ALF by stimulating the sodium absorption, so also preventing immersion and immobilization of the ciliated epithelium [62][63][64]111]. Based on protein sequencing, Anand et al [112] identified a S1/ S2 cleavage site in SARS-CoV-2 that can mimic the proteolytic activation of human ENaC: the virus can hijack several proteases that are involved in the activation and regulation of ENaC (TMPRRSS2, furin, prostasin, and matriptase [113][114][115]), furin in particular in view of a unique furin insertion site in its S protein [112].…”
Section: Interactions Of Saline With Sars-cov 2]mentioning
confidence: 99%
“…The pharmacological/pharmacodynamic effects of saline are effectuated at concentrations already reached by isotonic saline. In vivo, the limited action of isotonic saline on the viral ACE2-receptor binding and SARS-CoV-2 replication [33,91,92] will be complemented by its effect on ciliary beating and the MCC for clearing virus [46,47,[69][70][71]. Overall, the complex interactions with NaCl, particularly those impacting with ACE2 and ENaC, suggest that a therapeutic strategy for recovering the balance between alveolar uid formation and reabsorption may contribute to the treatment for alveolar lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…These layers need to be appropriately hydrated in the lungs and airways, allowing the cilia to beat properly and move the mucus and transporting trapped pathogens and particles. The height of the ALF and hydration of the periciliary liquid layer depend on opposing mechanisms in water transport: the outward chloride (Cl -) secretory transport through apical chloride channels (CFTR and CACC mediated), and the inward movement of water following active (re)absorption of Na + through apical sodium channels ENaC, this in concertation with the basolateral Na + /K + -ATPase, located in the ciliated cells [42,[70], [71]]. Whereas many more ion transport processes are involved, it is to note that the upper layer of ASL likely contains high concentrations of ions above 100mM, while the periciliary liquid layer normally contains NaCl in an amount below 50mM (< 0.29%), which normally ensures and maintains effective transepithelial transport of ions and water, as allowing effective ciliary beating [71].…”
Section: Role Of Saline In the MCCmentioning
confidence: 99%
See 1 more Smart Citation